(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wanna C, Boonman N, Phakpaknam S, Pikulthong V, Jaitrong W, Soi-Ampornkul R. 2022. Species diversity of subterranean ants in Rangsit Marsh, Khlong Luang District, Pathum Thani Province, Thailand. Biodiversitas 23: 1283-1292. The present study aimed to compare species diversity and abundance of subterranean ants in three habitats: scrub forest, forest plantations, and glades at Rangsit Marsh, Khong Luang District, Pathum Thani Province, Thailand. The ant samples were collected twice a month during the rainy season (June-August 2019) and dry season (September-November 2019) using a pitfall trap in the soil. A total number of 6,305 individuals belonging to 4 subfamilies, 16 genera, and 16 species of ants were recorded. The subfamilies Myrmicinae comprising 6 species were the most prevalent, followed by 4 species of Formicinae, 3 species of Dolichoderinae, and 3 species of Ponerinae. The Shannon-Wiener species diversity index indicated the diversity was the highest in the glade (1.951), followed by the forest plantation (1.635), and lastly the scrub forest (0.419). Sorensen’s similarity coefficient to determine the similarity in community composition was highest between the forest plantation and the glade at 63.40%, and then between the scrub forest and the forest plantation at 44.30%, and between the scrub forest and the glade at 39.60%. This indicated that both ant species diversity and community composition were distinctly varied in these three sites. The rainy season revealed higher species richness than the dry season. The highest occurrence of ant species was for Iridomyrmex anceps (Roger, 1863), which was recorded as uncommon and was the most abundant species in the glade, while Anoplolepis gracilipes (Smith, 1857) and Carebara diversa (Jerdon, 1851) were the most abundant species in the scrub forest and forest plantation, respectively. Therefore, this study revealed that different habitat types and seasons resulted in differences in subterranean ant species diversity.